Electrodeposition of nickel/copper multi-nanolayer by dual bath technique at ambient temperature - Abdullah, Sharifah Sakinah (2017)
The electrodeposition of Nickel/Copper (Ni/Cu) multi-nanolayer coating has been carried out on Cu substrate by using dual bath technique. The electrodeposition process was carried out at electrolyte temperatures of 25 °C, 40 °C, and 60 °C. The Watts electrolyte and Cu (II) sulphate solutions have been chosen for this experimental work because it produced a good surface coating. This work aims to produce different sublayer thiclmesses (20 nm, 40 nm, 60 nm, 80 nm and 100 nm) with thickness ratio of 1: 1. The work also involved a study on the effect of different sublayer thickness, the effect of multiple nanolayers with different compositions of layer thickness (Ni:Cu = 2:1, 1:1 and 1:2) and the effects of different electrolyte temperatures. The production Ni/Cu multi-nanolayer samples was conducted by using current densities of Ni and Cu at 0.0527 A•cm"2 and 0.0505 A•cm"2 respectively. The (FESEM) image of Ni/Cu multi-nanolayer coating showed that the sublayer thickness of 20 nm exhibited the smallest compact cluster of cauliflowerlike appearance. The Focus ion beam FESEM images it was proven that all respective samples (20 nm, 40 nm, 60 nm, 80, and 100 nm) were truly exist and the multi-nano layer structures are formed alternately of Ni and Cu layer. The uniformity of coating composition was studied using coating composition while phase deposition presence was evidence by using X-ray Diffraction (XRD) respectively. The double-like peaks ofXRD data indicate the pattern of alternate multilayer which confirmed the existence of distinctive Cu and Ni layers with each of them having their own lattice parameter. The vickers hardness result showed that the sublayer thickness of 20 nm has highest hardness value of 504.32 Hv. The composition of the layer with the ratio of 2: 1 for Ni/Cu coating was found to contribute the highest hardness value which is 507 .54 Hv presenting an increase of 89 %. In addition, the microhardness of Ni/Cu multi-nanolayer reached its maximum hardness value 504.34 Hv at electrolyte temperature of 25 °C. The trends of the hardness values are in line with the corrosion resistance study on the coated samples. The corrosion properties of corrosion current density and the corrosion potential for 20 nm showed a shift towards the more positive regions. So, the sublayer thickness of 20 nm had excellent effect on the corrosion resistance. Ni/Cu multi-nanolayer system with the ratio of 1 :2 presented the highest corrosion resistance among other multi-nanolayer system. The best corrosion resistance was attributed to coating samples prepared at electrolyte temperature of 25 °C, based on the results obtained from morphological analyses, hardness and corrosion. In conclusion, this study has evidenced that Ni/Cu multi-nanolayer successfully enhanced the physical and chemical properties of the coating. Ni/Cu multi-nanolayer